The Role of Recognition and Career Development Rewards in Fostering Teacher Engagement: A Systematic Review - Mas Ning Zahroh; Rita Retnowati; Hendarman Hendarman (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This study investigates the relationship between recognition and career development rewards and their impact on teacher engagement through a systematic review of 15 selected peer-reviewed articles published between 2019 and 2025. The review examined diverse educational contexts, including early-career teachers, private and public schools, and various subject areas, to identify how recognition and career development initiatives influence teacher motivation, satisfaction, and retention. Findings reveal that recognition of achievements, appreciation, and supportive organizational environments significantly enhance intrinsic motivation and emotional engagement, particularly among early-career teachers. Career development rewards, including mentoring, training, coaching, and structured reward systems, were found to contribute to long-term motivation, job satisfaction, and retention, especially in private school settings. Several studies highlight gaps in the implementation of effective recognition systems, showing that teachers often perceive insufficient acknowledgment of their performance, which can reduce engagement and increase turnover intentions. Moreover, the synergistic integration of recognition and career development rewards produces the most substantial improvements in teacher engagement, suggesting that organizations should address both psychological and professional growth needs. This systematic review underscores the importance of combining recognition programs with career development strategies to foster sustainable teacher engagement and improve overall educational outcomes. In conclusion, integrating recognition and career development rewards is a practical and effective approach to enhancing teacher engagement across diverse educational contexts.